LIFE STORIES OF PUNTARENAS: THE NURSING HOMES OF ESPARZA AND MIRAMAR, 2015-2016 - Cousin Brenes, Kathia (2019)
This article intends, through the technique of content analysis, to analyze the life stories of the residents of the retirement homes of Esparza and Miramar, in the period 2015-2016, to investigate the different ways in which memory is reconstructed and, at the same time, highlighting the socio-cultural effects of this construction. From this study, it can be concluded that among the participants there is a tendency to evoke the past as a better time, in relation to significant events in their lives.